Getting to the Truth: Ethics, Trust, and Triage in the United States versus Europe during the Covid-19 Pandemic - Orfali, Kristina (The Hastings Center report, 2021)
Ethical issues around triage have been at the forefront of debates during the Covid-19 pandemic. This essay compares both discussion and guidelines around triage and the reality of what happened in the United States and in Europe, both in anticipation of and during the first wave of the pandemic. Why did the issue generate so many vivid debates in the United States and so few in most European countries, although the latter were also affected by the rationing of health care resources? Are countries with socialized health care systems better equipped to face the hard choices of triaging? Important lessons in transparency, trust, and accountability for policy-makers can be drawn from this comparison, demonstrating that fostering public involvement and ethical debate remains a critical element for the sustained acceptance of any triage plan.